2017
DOI: 10.1111/jace.14769
|View full text |Cite
|
Sign up to set email alerts
|

Fretting fatigue wear behavior of Y‐TZP dental ceramics processed by non‐conventional microwave sintering

Abstract: The fretting wear behavior of self‐mated Y‐TZP dental materials obtained by nonconventional microwave and conventional sintering has been investigated. Two 3Y‐TZP materials, a widely utilized commercial dental ceramic (LAVA) and a lab‐prepared 3Y‐TZP powder based equivalent have been assessed. Relative density and mechanical properties as well as the grain size variations upon sintering have been evaluated. After exposure to selected gross slip regime fretting wear conditions, the wear tracks have been charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…In general, the study suggests that microwave sintering of zirconia can result in comparable mechanical properties and high degrees of densification comparable to those achieved with conventional sintering systems at lower dwell temperatures and significantly shorter sintering times [50][51][52][53][54]. Moreover, some studies have demonstrated that microwave-sintered specimens exhibit enhanced crystallinity [55] and improved mechanical properties [18,49,56].…”
Section: Microwave Sintering Of Zirconiamentioning
confidence: 67%
“…In general, the study suggests that microwave sintering of zirconia can result in comparable mechanical properties and high degrees of densification comparable to those achieved with conventional sintering systems at lower dwell temperatures and significantly shorter sintering times [50][51][52][53][54]. Moreover, some studies have demonstrated that microwave-sintered specimens exhibit enhanced crystallinity [55] and improved mechanical properties [18,49,56].…”
Section: Microwave Sintering Of Zirconiamentioning
confidence: 67%
“…19,29,30 Sliding moves the microcontacts along, thus resulting in the observed scratches. 18,25,[31][32][33] Such spalling is particularly deleterious, since the greater surface roughness of the exposed regions may also damage the counterbody-in the oral cavity this can result in wear of antagonist teeth. The microcracks are randomly oriented, and not observed to be accompanied by transformation to the monoclinic phase, which indeed, inside the scars, was not observed at all.…”
Section: Methodsmentioning
confidence: 99%
“…The microcracks are randomly oriented, and not observed to be accompanied by transformation to the monoclinic phase, which indeed, inside the scars, was not observed at all. [23][24][25][26][27][31][32][33][36][37][38] , with pitting from particle pull-out indicated in Refs. 29 In some isolated regions of the wear scars, exposed patches of major roughness can also be observed ( Figure 8C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] In the fretting fatigue failure process, combining action with the fatigue behavior and wear damage of interface surfaces, it leads to the component occurring fatigue crack initiation, propagation and final failure. [7][8][9] Therefore, the objective of this work is to further study on tribo-chemical and fatigue behavior of torsional fretting fatigue. In addition, the frictional behavior in the fretting process is also discussed.…”
Section: Introductionmentioning
confidence: 99%